From CSR Narratives to Accountable Practice in Philippine Education: Governance, Evidence, and Credible Reporting - Hazel S. Osano; Anik Yuesti; Joel Arante Alve (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar., 2026)
CSR in Philippine education was increasingly judged by what could be shown, not only what was claimed. A desk-based review of recent peer-reviewed studies and current reporting and quality guidance mapped how accountability expectations shifted toward clear criteria, consistent indicators, and traceable decisions. Evidence pointed to a common gap: reports often highlighted activities and beneficiaries but rarely tracked outcomes over time or explained how key decisions were made. Where accountability practice was stronger, roles were defined, a small set of material commitments was monitored, and limitations were stated plainly. Overly broad reporting expectations without matching capability produced compliance fatigue and encouraged symbolic disclosure. A right-sized approach emerged as the most workable path, linking CSR to quality routines and focusing measurement on equity, learner protection, staff welfare, and community outcomes.